The “curse” of teaching in Polish proverbs - Hordy, Mirosława (Poznańskie Studia Slawistyczne, 2024)
The article discusses proverbs negatively evaluating the work of teachers as recorded in paremiographical dictionaries of the Polish language of the 19th and 20th centuries. The socio-historical context of this profession in Poland from its inception to the beginning of the 20th century is presented, and the literary and textual uses of the units in question are analysed. The history of the profession fully justifies the negative evaluation contained in the proverbs. The attestations of usage in corpus and Internet resources of contemporary Polish indicate that this assessment is still valid. The most widely used proverb in recent decades is Obyś cudze dzieci uczył!, as well as the phraseological expression derived from it, cudze dzieci uczyć. The noted modifications of some analysed units are an example of contesting the negative image of the teaching profession fixed in this stock of the Polish language.